Exploring the Developmental Progression of Endosperm Cavity Formation in Maize Grain and the Underlying Molecular Basis Using X-Ray Tomography and Genome Wide Association Study - Liao, Shengjin; Zhang, Ying; Wang, Jinglu; Zhao, Chunjiang; Ruan, Yong-Ling; Guo, Xinyu (Frontiers in Plant Science, 2022)
Endosperm cavity (EC) in maize grain reduces yield and causes grain breakage during mechanical harvesting, hence representing a major problem in maize industry. Despite this, little is known regarding the biological processes governing EC formation. Here we attempted to address this issue by (i) determining the spatial and temporal progression of EC in a non-invasive manner and (ii) identifying candidate genes that may link to the formation of EC by using GWAS. Visualization and measurement using X-ray micro-computed tomography established that EC first appeared at the central starch endosperm at about 12 days after pollination (DAP) and became enlarged thereafter. GWAS-based screening a panel of 299 inbreed lines with a wide range of EC size identified nine candidate genes that showed significant association with EC formation. Most of the candidate genes exhibited a decrease at 12DAP, coinciding with the timing of EC appearance. Among them, ZmMrp11 was annotated as a member encoding a multidrug resistance-associated protein that has been shown in other studies to sequestrate toxic metabolites from cytosol to vacuole, thereby detoxifying cellular environment. This, together with reduced expression of ZmMrp11 in maize grains from 12 DAP, prompt us to propose that low expression of ZmMrp11 may block cellular detoxification in the maize endosperm cells, leading to cell death, and ultimately the formation of EC.